Engagement of husbands in a maternal nutrition program substantially contributed to greater intake of micronutrient supplements and dietary diversity during pregnancy: Results of a cluster-randomized program evaluation in Bangladesh - Nguyen, Phuong Hong; Frongillo, Edward A.; Sanghvi, Tina; Wable, Gargi; Mahmud, Zeba; Tran, Lan Mai; Aktar, Bachera; Afsana, Kaosar; Alayon, Silvia; Ruel, Marie T.; Menon, Purnima (Elsevier, 2018)
A nutrition-focused MNCH program that promoted and facilitated husbands’ engagement during their wives’ pregnancies significantly improved husbands’ awareness, knowledge, self-efficacy, and support. These improvements substantially explained the program's impact on women's intake of micronutrient supplements and dietary diversity. Targeting wives and husbands and designing activities to engage men in maternal nutrition programs are important to maximize impact.